2011
DOI: 10.5089/9781463923280.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Precautionary Reserves for Low-Income Countries: A Cost-Benefit Analysis

Abstract: This paper develops a cost-benefit approach that helps to quantify the optimal level of international reserves in low-income countries, focusing on the role of reserves in preventing and mitigating absorption drops triggered by large external shocks. The approach is applied to a sample of 49 LICs over the period 1980-2008 to yield estimates of the likelihood and severity of a crisis. The calibration results suggest that the standard metric of three months of imports is inadequate for countries with fixed excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Crispolti and Tsibouris (2011), for example, found that lowincome countries with reserves of three or more months import cover were better able to smoothly consume and absorb the effects of external shocks. Dabla-Norris, Kim, and Shirono (2011) reported similar results, but also noted that optimal reserve holdings can be sensitive to country fundamentals and exchange rate regimes. Moreover, the authors also report that reserves only provide a temporary and partial solution to systemic vulnerabilities.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Crispolti and Tsibouris (2011), for example, found that lowincome countries with reserves of three or more months import cover were better able to smoothly consume and absorb the effects of external shocks. Dabla-Norris, Kim, and Shirono (2011) reported similar results, but also noted that optimal reserve holdings can be sensitive to country fundamentals and exchange rate regimes. Moreover, the authors also report that reserves only provide a temporary and partial solution to systemic vulnerabilities.…”
Section: Introductionsupporting
confidence: 78%
“…Following Dabla-Norris, Kim, and Shirono (2011), shocks are identified if the annual percentage change of one or more of six variables (external demand, terms-of-trade, FDI, aid, remittances and climatic shocks) falls below the tenth percentile in the left- 1960 1966 1972 1978 1984 1990 1996 2002 2008 2014 US $Billions tail of the country-specific distribution. The binary crisis dummy variable then takes a value of 1 if both of the following conditions hold: (1) the post-shock two-year average level of real absorption per capita falls below the pre-shock three-year trend; and (2) growth of real absorption per capita is negative.…”
Section: Exogenous Shocks and The Nature Of Crises In Small Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…He quantifies the reserve level that a country must be held by weighting the costs of adjustment resulting from external imbalances against the opportunity cost of holding reserve 1 [4]. 1 The total cost of adjustment is given by where is the amount of external imbalance, is the propensity to import. While the opportunity cost of holding reserves is the difference between the rate of return on social capital and the rate of return on international reserves Frenkel and Jovanovic define reserves as a buffer stock to accommodate stochastic fluctuations in external payments imbalances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been beliefs that reserves can reflect economy's ability to deal with cash inflows sudden stops shocks. Low income countries are more vulnerable to shocks of sudden stops inflows such as terms-of-trade shocks, a natural disaster or political instability, which result high macroeconomic volatility imposes large welfare costs, thus high reserves has been considered as insurance against the risk of cash inflow sudden stop crises [1]. This mean that the most important problems face low income countries is how to meet emergency financing needs, especially if the country reliance on international trade to import substantial amounts of its necessity needs, in the same time, rely on noncompetitive export sectors to generate most of its foreignexchange inflows.…”
Section: Introductionmentioning
confidence: 99%